Ijtihād-Based Politics: The Muhammadiyah Political Participation in Post-Soeharto - Asyari, Suaidi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
Founded in 1912, Muhammadiyah claims to be the largest puritan-modernist Islamic organisation not only in Indonesia but also in the world, with more than 25 million followers. Originally Muhammadiyah was purely a religious organisation. However, after the declaration of Indonesian independence in1945, particularly after Masy'umi -of which Muhammadiyah was one of its special membership - was transformed into a political party, Muhammadiyah has been involved in Indonesian politics in one way or another. Since it was founded, Muhammadiyah promotes ijtihad as opposed to ijma' as in the case of the Nahdlatul Ulama the largest traditionalist Islamic organization founded in 1926. However, it was after the collapse of New Order regime that Muhammadiyah started to associate its political role by combining its basis of worldview that is ijtihad with political attitudes of its leaders.DOI: 10.15408/sdi.v15i1.537